Seasonal variations of household costs of illness in Burkina Faso - Sauerborn, Rainer; Nougtara, A.; Hien, M.; Diesfeld, Hans J. (Social science & medicine, 1996)
This paper assesses the seasonal variations of the time and financial costs of illness for rural households in Burkina Faso. It is based on a multiple round survey of 566 households, which included a time allocation study. The economic parameters of households which influence health seeking behavior changed substantially between the dry and rainy seasons: revenues fell in the rainy season and were exceeded by expenditures. Household production was at its peak in the rainy season resulting in significantly higher opportunity costs of time. At the same time illness perception changed: in the rainy season, significantly fewer illness episodes were perceived, and of those, the proportion perceived as severe decreased over-proportionally. Households shifted their healer choice in the rainy season away from high cost treatment, such as the hospital and dispensary, to low cost home treatment. For all these reasons, households incurred significantly fewer costs of illness in the rainy season (27% of dry season costs). Household health care expenditures were reduced to 16 of dry season levels, the time costs incurred by healthy household members to tend to the sick was reduced to 15 and the time costs of work incapacity due to sickness fell to about 12 of dry season levels. The authors stress the need to carry out research in all relevant seasons when studying health seeking behavior and the household costs of illness in order to avoid serious seasonal bias. They suggest policy options to increase health care utilization in the rainy season by reducing the financial and time costs of access to health care. Finally, the authors put forward a hypothesis to be tested by future research: They argue that the cognitive (changes in illness perception) and behavioral changes (different health care seeking) reflect the high opportunity costs of time and the low availability of cash households face during the rainy season. The paper discusses the negative implication that untreated illness has on the health status of household members.
Elektronische Reproduktion der Druck-Ausgabe 24. Februar 1999
Gesehen am 23.10.2024